Pengaruh Pengembangan Strategi Marketing Terhadap Peningkatan Brand Awareness Pada Coffee Shop Era Cafe - Rendy Permana; Melyona Zenia Rabbil; Niken Sandora (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This study examines the effect of marketing strategy development on brand awareness improvement at Era Cafe using a quantitative empirical approach within a descriptive-causal framework. Data were collected from consumers who interacted with the café through direct visits and digital platforms, employing structured questionnaires and supported by secondary data from social media activities. The findings indicate that the development of marketing strategies, particularly through product innovation, digital content consistency, and promotional attractiveness, plays a significant role in strengthening brand awareness. Furthermore, the results reveal that the impact extends beyond cognitive recognition toward behavioral outcomes, including customer loyalty, revisit intention, advocacy, and purchase decisions. This demonstrates that effective marketing strategies contribute not only to brand positioning but also to sustained consumer engagement and long-term business performance. These findings provide practical implications for business actors in designing strategic marketing initiatives that are both impactful and sustainable.